Edukasi Peran Masyarakat Dalam Tata Kelola Program Food Estate Singkong Di Desa Tewai Baru, Kecamatan Sepang, Kabupaten Gunung Mas - Kisno Hadi; May Linda Sari (Sekolah Tinggi Teologi Gereja Kalimantan Evangelis, 2025)
This Community Service Program (PkM) focuses on educating and increasing community knowledge on the cassava food estate policy in the rural of Tewai Baru, Sepang District, Gunung Mas Regency. The rural of Tewai Baruis selected as one of the rural areas which is included in the cassava food estate program. Food estate program is initiated by the Central Government under the National Strategic Project (PSN) scheme through in Presidential Regulation Number 109/2020. The program is implemented by the Ministry of Defense in collaboration with the Ministry of Agriculture. The subjects of PkM are the rural government and the local community through discussion and socialization, then they can adapt and support the cassava food estate program. Both subjects get benefits and positive impacts for optimizing existing resources to improve the rural economy, particularly for residents directly involved in the cassava food estate program. The PkM activity was conducted in one day using a counseling method at the office of rural, attended by 23 participants, a.i the rural of head, rural secretary and officials, chairperson and members of the Rural Representative Body, community leaders, neighborhood heads (RT), traditional leaders, and the local military representative (Babinsa). This PkM activity was supported by the Institute for Research and Community Service (LPPM) of Palangka Raya Christian University. Hopefully, this program will be beneficial for the resident rural of Tewai Baru, especially in supporting food security and improving the community’s economy. For lecturer, PkM activities can be a means of socialization and building compus-rural relation as well as between lecturers and the local community. In addition to implementing academic knowledge and theories taught on campus, also provide opportunities to learn from community experiences to be shared with students at campus.